Pengaruh Penambahan Kalsium Karbonat (CaCO₃) Terhadap Kekerasan Material HDPE/LDPE - Enggita, Asadian Puja; Ikhsandy, Ferry; Jaman, Winda Sri; Syafaatullah, Achmad Qodim (REACTOR: Journal of Research on Chemistry and Engineering, 2025)
Plastic waste recycling has been extensively studied, particularly in applications such as paving blocks, asphalt mixtures, and composite boards. One critical parameter affecting the quality of these products is material hardness. This study examines the effect of CaCO₃ addition on the hardness of polymer composite materials. The preparation process involved collecting, washing, drying, sorting, and shredding plastic waste, followed by mixing High Density Polyethylene (HDPE) and Low-Density Polyethylene (LDPE) at a ratio of 1:5. Calcium carbonate (CaCO₃) was added at varying concentrations (0%; 0,5%;1,0%; 1,5%, and 2,0%), and the mixture was melted using an extruder and subsequently molded. The results indicate that the addition of 1,5% CaCO₃ yields the highest and most stable hardness value across three tests, achieving 4,77 HV with a standard deviation of 0,0577. Furthermore, microstructural analysis reveals that up to 1,5% CaCO₃ leads to the most uniform filler distribution, optimizing both hardness and material stability. This study reveals that increasing CaCO₃ concentration enhances composite material hardness when evenly distributed and homogeneous. However, excessive CaCO₃ concentration may result in agglomeration, negatively impacting composite properties.